1994
DOI: 10.1182/blood.v83.12.3449.3449
|View full text |Cite
|
Sign up to set email alerts
|

Genomic instability of microsatellite repeats and its association with the evolution of chronic myelogenous leukemia [see comments]

Abstract: Tumorigenesis has been shown to proceed through a series of genetic alterations involving protooncogenes and tumor-suppressor genes. Investigation of genomic instability of microsatellites has indicated a new mechanism for human carcinogenesis in hereditary nonpolyposis colorectal cancer and sporadic cancer and this instability has been shown to be related to inherited predisposition to cancer. This study was conducted to determine whether such microsatellite instability is associated with the evolution of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(42 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…Recent studies support the notion that the lack of mismatch repair increases mutagenesis and leads to tumour progression (Bicknell et al, 1994;Lazer et al, 1994). In accordance with these studies, in some types of neoplasms a higher incidence of MSI was observed in more advanced stages of malignancy (Chong et al, 1994;Han et al, 1993;Wada et al, 1994). To determine if MSI might play an important role in the progression of AML, we analysed MSI in AML at diagnosis, remission, and relapsed stages for each of 17 individuals.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Recent studies support the notion that the lack of mismatch repair increases mutagenesis and leads to tumour progression (Bicknell et al, 1994;Lazer et al, 1994). In accordance with these studies, in some types of neoplasms a higher incidence of MSI was observed in more advanced stages of malignancy (Chong et al, 1994;Han et al, 1993;Wada et al, 1994). To determine if MSI might play an important role in the progression of AML, we analysed MSI in AML at diagnosis, remission, and relapsed stages for each of 17 individuals.…”
Section: Resultsmentioning
confidence: 72%
“…Recent studies of MSI during cancer development have found that in some tissue types MSI predominates in poorly differentiated and advanced tumours (Chong et al, 1994;Han et al, 1993;Lothe et al, 1993). Wada et al (1994) reported a high frequency (53%) of MSI in the DNA of blast phase leukaemic cells from patients with chronic myelocytic leukaemia (CML), and concluded that the development of MSI was a late genetic event in the evolution of CML to blastic crisis. This loss of fidelity in replication and repair mechanisms may indeed contribute to the progression of a more malignant disease, and may not merely be a sign of progression.…”
mentioning
confidence: 99%
“…Chronic myelogenous leukaemia is due to the Philadelphia chromosome, encoding the Bcr/Abl fusion. Careful epidemiological modelling has revealed that it can be explained by a single mutation model (Michor et al, 2006), despite the fact that its genome is quite unstable and that other genetic abnormalities are frequently observed, particularly when the disease progresses towards acute phase (Wada et al, 1994). This relative low number of driving abnormalities holds true for most translocation-associated leukaemias.…”
Section: Some Leukaemias Are Quasi-monogenicmentioning
confidence: 99%
“…Loci and the primer sequences for microsatellite analysis in this study were shown in Table 2 and have been described previously. [17][18][19] The locus D9S171 on 9p and two loci (D12S89 and D12S98, which flank the TEL gene) on 12p were selected because of a relatively high frequency of LOH in these loci in childhood hematologic malignancies. The polymerase chain reaction (PCR) for amplifying each region was performed on 0.2 µg DNA template in a total volume of 50 µL, containing 2 µmol/L each primer, 200 µmol/L dNTP, 10 mmol/L Tris-HCl (pH 8.3), 50 mmol/L KCl, 1.5 mmol/L MgCl 2 and 1.25 U Taq DNA polymerase (Perkin-Elmer Cetus).…”
Section: Microsatellite Analysismentioning
confidence: 99%